Electrical conductivity test on castor bean seeds - Da Silva, Líbia Belisário [UNESP]; Martins, Cibele Chalita [UNESP] (Universidade Estadual de Londrina, 2009)
The aim was to study the efficiency of electrical conductivity test in evaluating the quality of castor seeds. Emergence of seedlings was evaluated in the field, with five seed lots of cv. AL Guarany 2002. The seeds were submitted to the following tests: germination; first count of germination; accelerated aging (45°C by 24 to 100% UR), emergence of seedlings in the field, rate of speed of development of seedlings and electrical conductivity, testing the periods (2, 4, 6, 8 and 24 hours) and the number of seeds (25, 50 and 75) in 75ml of distilled water conditioning to 25°C. A completely randomized design was used. The averages were compared by the Tukey test at 5%. The mean laboratory and field test data were correlated. Electrical conductivity test for 4 hours with 25 seeds and 6 hours with 50 seeds, and the rate of speed emergency proved efficient in the selection of lots vigor by providing information equivalent to the emergence of seedlings in the field.
Teste de condutividade elétrica para sementes de mamoneira
Keywords: Castor bean; Ricinus communis L; Speed emergency; Vigor